MAKNA “AL-IQTIṢÂD ” DAN KORELASINYA DENGAN EKONOMI KONTEMPORER (TELA’AH AYAT-AYAT EKONOMI) - Luayyin, Reza Hilmy; Mohammad Arifin; Muhammad Nabat Ardli (JSE: Jurnal Sharia Economica, 2024)
Many communities still misconception the concept of Islamic economics. In fact, a significant portion of the Muslim population itself is somewhat unfamiliar with the terms associated with Islamic economics. The terms "Qaṣd" or "al-Iqtiṣâd," which form the basis for translating economics in Islam, remain a subject of debate among experts. The definition of "Qaṣd" or "al-Iqtiṣâd" serves as the foundation for the economic thought of scholars. The Islamic economic system is derived from the Qur'an, serving as the fundamental basis for Muslims. This research utilizes a qualitative descriptive approach, employing normative analysis and falling under the category of literature-based research. The study focuses on examining the fundamental meaning of economics in Islam and its correlation with contemporary economics. The results from data analysis and discussions indicate: 1) The meaning of "Qaṣd" or "al-Iqtiṣâd" in the Qur'an has four dimensions, namely simplicity, straightness, moderation (justice), and proximity (not too distant). 2) The concept of contemporary Islamic economics implies that the Islamic economic system is grounded in Sharia to construct the worldview of individuals, policies, and goals different from the dominating capitalist and sociological (communist) economic systems. 3) The correlation of the terms "Qaṣd" or "al-Iqtiṣâd" with contemporary economics is inherent in the Islamic economic system itself, which should ideally be ingrained in economic activities and be based on values or divine norms as the foundation for all aspects of life. When divine norms or values serve as the foundation, balance and prosperity in both the worldly and the hereafter can be achieved.